The Effectiveness of High Quality Supplementary Cementitious Materials for Mitigating ASR Expansion in Concrete with High Alkali Content - Prasetia, I. (Engineering, Technology & Applied Science Research, 2015)
Alkali silica reaction (ASR) is influenced by external factors such as the surrounding environment of high alkalinity. Countries with cold climate have a high probability to be exposed to high concentrations of NaCl solution by the deicing salt. This condition will lead to serious ASR problems in concrete, if the aggregates contain reactive silica. The main research work in this paper is to investigate the effect of 15% replacement ratio of high quality fine fly ash (FA15%) and 42% replacement ratio of blast furnace slag (BFS42%) on the ASR mitigation in concrete with different alkali amount inside the pore solution. The experiments were conducted according to the accelerated mortar bars experiment following the JIS A1146 mortar bar test method. In addition, post-analysis such as observation of ASR gel formation by the Uranyl Acetate Fluorescence Method and observation of thin sections using a Polarizing Microscope were also conducted. The mortar bar tests show a very good mitigation effect of supplementary cementitious materials (SCMs). The results show that only small ASR expansions, which can be categorized as “innocuous”, occurred for specimens with 1.2% Na2Oeq using FA15% and BFS42%. However, larger alkali amount inside the system will require more SCMs amount.